Quickly SOFA Score Can Be Used as a High-Efficiency Classi-fied Method for COVID-19 Infected Patients - Ke FENG; Zhongwei CHEN; Bin MEI; Xing DU; Xufeng FU (Tehran University of Medical Sciences, 2020)
No Abstract